(untitled) (Journal of Hama University, 2024)
The research aims to design a proposed training program using transitional speed, agility and Kinetic speed exercises for junior football players (under 12 years) and to know its effect on some harmonic abilities of the sample under study. The experimental method was used for one group and by using measurement (pre-post) on (20) players from the junior category (under 12 years) from a group of football academies and schools in the governorates of Damascus and Damascus countryside, in the period from 5/10/2021 to 5/4 / 2022, on the industrial stadium (Bocce) in Al-Fayhaa Sports City in Damascus. The most important results of the research were that alternating transitional speed, agility and Kinetic speed exercises in the training sense had a positive effect on improving the coordination abilities of junior football players (under 12 years old).